Factors affecting carcass characteristics in exotic, desi and crossbred pigs - SINGH, S K; JHA, D D; NATH, S; SINGH, R L; PANDEY, R N (The Indian Journal of Animal Sciences, 2013)
Pigs (380) belonging to 6 genetic groups (151 Large White Yorkshire, 47 Landrace, 26 Hampshire. 27 T and D. 71 LargeWhite Yorkshire x desi haltbreds and 58 des;) of the pig breeding farm, including 193 pigs supplied by private pig breedersof urban and rural areas in ana around Ranchi. were slaughtered and utilized to study carcass characteristics. Genetic group.weight and age of animals at slaughter had significant influence on all the carcass traits under study except effect of genetic group on back fat thickness and age of animals on dressing percentage. All the carcass traits were free from the effect of sex. Similarly interaction between genetic group and sex had no effect on any oftl'e carcass traits except for dressing percentage.